Elevated levels of enteric IgA in an unimmunised mouse model of Hyper IgM syndrome derived from gut-associated secondary lymph organs even in the absence of germinal centres - Hernandez-Cazares, Felipe; Maqueda-Alfaro, Raul Antonio; Lopez-Saucedo, Catalina; Martinez-Barnetche, Jesus; Yam-Puc, Juan Carlos; Estrada-Parra, Sergio; Flores-Romo, Leopoldo; Estrada-Garcia, Teresa (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Patients with Human Hyper IgM syndromes (HIGM) developed pulmonary and gastrointestinal infections since infancy and most patients have mutations in the CD40 ligand (CD40L) gene. Most HIGM patients compared to healthy subjects have higher/similar IgM and lower IgG, and IgA serum concentrations but gut antibody concentrations are unknown. CD40L on activated T-cells interacts with CD40 on B-cells, essential for the formation of germinal centres (GCs) inside secondary lymphoid organs (SLOs), where high-affinity antibodies, long-lived antibody-secreting plasma cells, and memory B-cells, are produced. C57BL6-CD40 ligand deficient mice (C57BL6-cd40l−/−), are a model of HIGM, because serum immunoglobulin concentrations parallel levels observed in HIGM patients and have higher faecal IgA concentrations. In mice, TGFβ and other cytokines induce IgA production. Aims To compare and evaluate B-cell populations and IgA-producing plasma cells in peritoneal lavage, non-gut-associated SLOs, spleen/inguinal lymph nodes (ILN), and gut-associated SLOs, mesenteric lymph nodes (MLN)/Peyer´s patches (PP) of unimmunised C57BL6-cd40l−/− and C57BL6-wild-type (WT) mice. Material and methods Peritoneal lavages, spleens, ILN, MLN, and PP from 8-10 weeks old C57BL6-cd40l−/− and WT mice, were obtained. Organ cryosections were analysed by immunofluorescence and B-cell populations and IgA-positive plasma cell suspensions by flow cytometry. Results In unimmunised WT mice, GCs were only observed in the gut-associated SLOs, but GCs were absent in all C57BL6-cd40l−/− SLOs. PP and MLN of C57BL6-cd40l−/− mice exhibited a significantly higher number of IgA-producing cells than WT mice. In the spleen and ILN of C57BL6-cd40l−/− mice IgA-producing cells significantly decreased, while IgM-positive plasma cells increased. C57BL6-cd40l−/− B-1 cells were more abundant in all analysed SLOs, whereas in WT mice most B-1 cells were contained within the peritoneal cavity. C57BL6-cd40l−/− B-cells in MLN expressed a higher TGFβ receptor-1 than WT mice. Mouse strains small intestine microvilli (MV), have a similar frequency of IgA-positive cells. Discussion Together our results confirm the role of PP and MLN as gut inductive sites, whose characteristic features are to initiate an IgA preferential immune response production in these anatomical sites even in the absence of GCs. IgA antibodies play a pivotal role in neutralising, eliminating, and regulating potential pathogens and microorganisms in the gut.